PRICE COMPETITION AND PROMOTIONAL ACTIVITIES ON THE PURCHASE BEHAVIOR OF YAMAHA MATIC MOTORCYCLES IN INDONESIA STUDY IN THE CITY OF KALIANDA LAMPUNG - Khil Wailmi (FEB - Universitas Lampung, 2021)
That price competition and Promotional Activities have a positive effect on purchasing decisions of 7,417 points. With weak correlation, Keywords. Price competition, promotional activities and purchasing decisions